2018
DOI: 10.32734/lwsa.v1i1.164
|View full text |Cite
|
Sign up to set email alerts
|

Mobilitas Sosial Penduduk Berbasis Industri Pariwisata Dalam Meningkatkan Status Sosial Ekonomi Masyarakat di Kota Gunung Sitoli, Nias Propinsi Sumatera Utara

Abstract: Pertumbuhan Kunjungan wisatawan ke Kabupaten Nias beberapa tahun belakangan menggambarkan peningkatan aktifitas sosialekonomi masyarakat Nias di bidang pariwisata. Peningkatan aktifitas sosial-ekonomi ini menjadi salah satu faktor pemicu mobilitas sosial penduduk dalam meningkatkan kesejahteraan masyarakat Nias. Penelitian ini bertujuan untuk menemukan jawaban apakah mobilitas penduduk Nias melalui aktifitas yang berbasis industri pariwisata dapat meningkatkan status sosialekonomi masyarakatnya; serta bagaiman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The existence of the tourism industry in the Special Economic Zone (SEZ) of Mandalika Kuta Lombok is very helpful to the local community in terms of employment. This result is supported by research conducted by Sismudjito et al, (2018) found that the development of the tourism industry can provide new employment and livelihood opportunities for the community who were previously unaware of the tourism industry. The tourism industry can provide new knowledge about employment, which is not only focused on agriculture and can help the community's economy and can increase income to meet family needs.…”
Section: Women's Employment Status Previous and Aftermentioning
confidence: 65%
“…The existence of the tourism industry in the Special Economic Zone (SEZ) of Mandalika Kuta Lombok is very helpful to the local community in terms of employment. This result is supported by research conducted by Sismudjito et al, (2018) found that the development of the tourism industry can provide new employment and livelihood opportunities for the community who were previously unaware of the tourism industry. The tourism industry can provide new knowledge about employment, which is not only focused on agriculture and can help the community's economy and can increase income to meet family needs.…”
Section: Women's Employment Status Previous and Aftermentioning
confidence: 65%
“…Nias Regency has the potential for natural/special interest, cultural/historical, and agro tourism objects, which are spread across the SOZIONA tourism economic area (Somi-Bozihona-Onolimbu-Nalawo) (Lase et al, 2018); Nias Selatan Regency has the leading sectors of agriculture, forestry and fisheries (Fau, 2018); tourism (Puspita, 2019); contributions and potential local taxes and fees are in the moderate category (Waoma, 2017); Nias Utara Regency has superior potential in the agricultural, forestry and economic sectors so that it contributes to the development of the Gross Regional Domestic Product (GDP) by 52.25% (2020-2022) (I lmiha, 2023); Nias Barat Regency has several potential tourist attractions, such as Pantai Sirombu (Sirombu B each), Pulau Asu (Asu Island), Pantai Gu'u (Gu'u Beach), Pantai Fari'i (Fari'i Beach), Pantai Ture (Ture B each), Pantai Fadaya (Fadaya Beach), Pantai Valaete (Valaete Beach), Pulau Bawa (Bawa Island ), Bale, Bu kit Hermon (Hermon Hill), Rumah Adat (Traditional Houses), and Batu Megalit (Megalithic Stones) in Lahomi Village, Lolozirugi Village, and Sisarahili Village (Liyushiana, 2019). Meanwhile, Gunungsitoli City has several potentials including the tourism sector (Sismudjito et al, 2018); and Micro, Small, and Medium Enterprises (UMKM) spread across 6 sub-districts, namely Gunungsitoli District (5,821), Gunungsitoli Selatan District (612), Gunungsitoli Utara District (844), Gunungsitoli Barat District (240), Gunungsitoli Idanoi District (914), and Gunungsitoli Alo'oa District (291) bringing a total of 8,722 business actors (Putra et al, 2018). Some of these potentials are important to be mapped through the Geographic Information System (GIS) (Maskun et al, 2021) or through the development of growth centers and their supporting areas in regional development in Nias Regency (G ulo, 2015).…”
Section: Introductionmentioning
confidence: 99%